Sosiologi Sastra dalam Novel Mei Merah 1998 Kala Arwah Berkisah Karya Naning Pranoto - Ayu, Rezki; Shomary, Sudirman (UIR Press, 2023)
The novel contains literary elements that can be studied using literary sociology theory. This research uses descriptive methods, hermeneutic data collection techniques, data analysis techniques, content analysis techniques and triangulation data validity techniques. The theory used in this research is Mana Sikana's theory (1986). The data source for this research is the 1998 novel Mei Merah Kala Arwah Bercerita by Naning Pranoto, which has 218 pages. The results of the research show that the Sociological Analysis of Literature in the Novel Mei Merah 1998, Kala Arwah tells the story, there are 13 data contained in the ethical aspect, namely 4 data related to responsibility, 5 data related to conscience, 4 data related to rights and obligations. There are 15 data aspects of culture, namely 6 data related to knowledge systems, 5 data related to religion, and 4 data related to art. There are 4 data in the philosophical aspect, namely 3 data related to material logic and 1 data related to formal logic.